2016
DOI: 10.3758/s13421-016-0649-0
|View full text |Cite
|
Sign up to set email alerts
|

Source credibility and the processing of refutation texts

Abstract: The knowledge revision components framework (KReC) outlines the basic comprehension processes and text factors that can be accentuated to increase the potential for knowledge revision during reading. The goal of the present study was to explore source credibility as one such text factor. In Experiment 1, we established the utility of a set of refutation texts in influencing knowledge revision. Participants read ten refutation and ten control texts. The participants had faster reading times and higher posttest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 78 publications
1
29
0
Order By: Relevance
“…Given that this resembles the information environment of our study with two conflicting positions, providing additional source information for both positions can be expected to further increase agreement with the correct information and therefore respective knowledge revision. A first study regarding the role of source information in refutation texts already showed that source information can have an effect on successful knowledge revision (Van Boekel et al, 2017). In that study, however, only the source credibility (i.e.…”
Section: Source Credibility Affecting Claim Agreementmentioning
confidence: 97%
“…Given that this resembles the information environment of our study with two conflicting positions, providing additional source information for both positions can be expected to further increase agreement with the correct information and therefore respective knowledge revision. A first study regarding the role of source information in refutation texts already showed that source information can have an effect on successful knowledge revision (Van Boekel et al, 2017). In that study, however, only the source credibility (i.e.…”
Section: Source Credibility Affecting Claim Agreementmentioning
confidence: 97%
“…Across three experiments, we sought to determine the effects of embedding positive and negative emotional content in refutation texts and whether such texts could successfully revise misconceptions about vaccines. The current design and procedure were similar to previous studies Van Boekel et al, 2017) wherein participants were asked to read a series of short stories that followed a narrative-informational format (Duke, 2000). The standard refutation texts included a brief introduction of a scene and two protagonists, an elaboration section that stated and refuted a targeted misconception about vaccines and explained the correct understanding conveyed via character dialogue, a filler section that continued the storyline, a correct-outcome sentence that stated the correct belief, a spillover sentence, and a section that concluded the story.…”
Section: Present Studiesmentioning
confidence: 59%
“…Misconceptions about controversial and non-controversial topics are alike in that they both deviate in substantive ways from the normative and best available evidence. At minimum, both require credible and plausible corrections to be revised (Kendeou & van den Broek, 2005;Lombardi, Bickel, Bailey, & Burrell, 2018;Rich, Van Loon, Dunlosky, & Zaragoza, 2017;Van Boekel, Lassonde, O'Brien, & Kendeou, 2017). However, controversial topics are distinguished by the involvement of multiple stakeholders whose incentives, ideas, and prior commitments are in conflict about how to resolve high-stakes issues (Johnson, 2015).…”
Section: Misconceptions About Controversial Topicsmentioning
confidence: 99%
“…For debunking, organizational sources seem more effective than individuals (van der Meer & Jin, 2020; Vraga & Bode, 2017) but only when information recipients actively assess source credibility (van Boekel et al, 2017). Indeed, source credibility may matter little when individuals do not pay attention to the source (Albarracín et al, 2017;Sparks & Rapp, 2011), and despite highly credible sources the continued influence of misinformation may persist (Ecker & Antonio, 2020).…”
Section: Source Effectsmentioning
confidence: 99%